Should I stay or should I go? Housing and residential mobility across OECD countries - Causa, Orsetta (OECD Publishing, 2020)
This paper delivers new evidence on the individual and policy drivers of residential mobility, covering a wide range of housing-related policies and conditions but also other relevant policy areas. The analysis uses household-level micro datasets allowing for an investigation of the drivers of the decision to move for a large number of OECD countries; as well for identifying differential policy effects across socio-economic groups, underscoring the distributional effect of policies. The evidence strongly supports the view that housing conditions and structural policies influence people's decisions and possibilities to move. A more responsive housing supply is associated with higher residential mobility, suggesting that reforming land-use and planning policies may facilitate moving by reducing house price differences across locations. Social cash and in-kind spending on housing are positively correlated with residential mobility. Higher housing transaction costs, including from transfer taxes, are associated with lower residential mobility, especially among younger households, which are more likely to be first time-buyers. Stricter rental regulations are associated with lower residential mobility, particularly for renters, low-educated and low-income households. Beyond housing policies, more generous cash income support to low-wage jobseekers and minimum income schemes embedded in social transfers are positively associated with residential mobility; while excessive job protection on regular contracts is negatively associated with mobility, particularly for youth, low-income and low-educated individuals
Keywords: Economics